Producing Pleasure in Indonesian Boys’ Magazine: Strategy to Control Boys’ Sexuality - Muria Endah Sokowati; Frizki Yulianti Nurnisya (The Journal of Society and Media, 2021)
The transition of political regime in Indonesia during 1995-2004 has implicated the dynamic discourse on gender ideology. It is reflected on the production of sex articles in Hai magazine, the only boys’ lifestyle magazine in Indonesia, for more than three decades. This paper attempts to analyze the sex articles in Hai magazine. Using Fairclough’s Critical Discourse Analysis, we found that the articles of safe and healthy sex socialization portray sex as a pleasing activity for teenage boys. However, sexual pleasure defined by Hai does not refer to Hai’s attempt to promote sexual freedom. This pleasure actually reflects the idea of normative sexuality. It is demonstrated in this scholarly work how the discourse of sexual pleasure produced by Hai magazine became a strategy to promote safe sex. Hence, it is being challenged that the promotion of safe sex strategy is a manifestation of Hai’s compromise toward the contestation of various ideas of sexuality existing in Indonesia in the 1990s and 2000s, during the transition of political regime in Indonesia, including the conservatism and sexual liberalism.